Influence of hybrid polymeric nanoparticle/thermosensitive hydrogels systems on formulation tracking and in vitro artificial membrane permeation: A promising system for skin drug-delivery - Grillo, Renato [UNESP]; Dias, Fabiana V.; Querobino, Samyr M.; Alberto-Silva, Carlos; Fraceto, Leonardo F. [UNESP]; de Paula, Eneida; de Araujo, Daniele R. (Elsevier, 2019)
In recent years, the development of hybrid drug delivery systems, such as hydrogels and nanoparticles, has gained considerable attention as new formulations for skin-delivery. Meanwhile, transdermal diffusion synthetic membranes have been used to assess skin permeability to these systems, providing key insights into the relationships between drug and nanoformulations. In this study, benzocaine-loaded poly-ε-caprolactone nanoparticles (BZC:NPs) were synthesized, characterized and incorporated into Poloxamer 407-based hydrogel (PL407). Benzocaine (BZC) was used as a drug model since has been commonly applied as a topical pain reliever in the last years. Hence, we developed a hybrid polymeric nanoparticle/thermosensitive hydrogels system and evaluated the in vitro permeation of the BZC, as well as nanoformulation tracking in an artificial membrane. In vitro permeation study was conducted in a vertical diffusion cell system using a Strat-M ® membrane model. BZC:NPs were prepared by coprecipitation method and their physicochemical stability measured before incorporating into the thermosensitive hydrogel. Also, viscosity measurements and sol-gel transition temperature were performed by rheological analysis. Different techniques, including microscopy, were used to tracking the nanoparticles on both receptor medium and synthetic membranes. Results showed high BZC encapsulation efficiency into NPs (93%) and good physicochemical stability before and after hydrogel incorporation. BZC in vitro permeation kinetics from NPs-loaded Poloxamer 407-based hydrogel presented slower permeation profile compared with the BZC: Poloxamer 407-based hydrogel. Also, NPs were observed into the diffusion cells receptor compartment after the in vitro permeation study. These results contribute to a better understanding the interaction between hydrogels, nanoparticles and synthetic membrane, as well as open perspectives for the development of new drug delivery systems for skin.
Keywords: Controlled release; Hybrid systems; Hydrogels; Nanoparticles; Permeation study; Synthetic membrane